A Co-ZnFe2O4 / Fe2O3-CNTs composite material for a lithium ion battery and a preparation method thereof

CN122977368APending Publication Date: 2026-10-27INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611490192.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

1、本发明改性碳纳米管在前驱体形成阶段直接引入,使MOF衍生颗粒能够与CNTs形成较为充分的接触,并在热处理后形成颗粒负载于CNTs骨架的复合结构。改性碳纳米管改善了活性颗粒的分散状态,并构建连续的导电网络,从而提高材料的电子传输能力和结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977368A_ABST
    Figure CN122977368A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electrochemical energy storage materials, in particular to a Co-ZnFe2O4 / Fe2O3-CNTs composite material for a lithium ion battery and a preparation method thereof, which comprises the following steps: S1, zinc nitrate hexahydrate, ferrous sulfate heptahydrate and a modified cobalt source are added into methanol, fully stirred and then ultrasonically treated to obtain a metal mixed solution; S2, a structure modifier is added to obtain a modified MOF / CNTs composite precursor; S3, centrifugal separation, washing and drying are carried out; and S4, heat treatment is carried out in a tube furnace, and the Co-ZnFe2O4 / Fe2O3-CNTs composite material is obtained after natural cooling. Through the synergistic effect of the modified cobalt source, the structure modifier and the three, the double-effect synergy of "ligand pre-anchoring-metal in-situ chelation" is realized, the high-density in-situ nucleation and uniform growth of the MOF precursor on the surface of the CNTs are formed, and the structural stability and the capacity retention rate in the cycle process are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage materials technology, specifically to a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries and its preparation method. Background Technology

[0002] With the development of new energy vehicles and energy storage technologies, higher requirements are being placed on the energy density, rate performance, and cycle life of lithium-ion batteries. The anode material is a crucial component of lithium-ion batteries; its specific capacity, conductivity, and structural stability during cycling all affect the overall battery performance. Currently, commercial lithium-ion battery anodes primarily use graphite materials, but graphite has a relatively low theoretical specific capacity (only 372 mAh g⁻¹). -1 The further application of anode materials in high-energy-density lithium-ion batteries is somewhat limited. Therefore, developing novel anode materials with high specific capacity and good cycle performance is of great significance.

[0003] Transition metal oxides possess high theoretical specific capacity and have become an important research direction for lithium-ion battery anode materials in recent years. Among them, ZnFe2O4 has a high lithium storage capacity, while Fe2O3 is abundant and has good chemical stability; both can participate in lithium-ion storage through conversion reactions. However, these metal oxides have relatively low electronic conductivity and undergo some volume changes during repeated charge-discharge cycles, which can easily lead to particle agglomeration, structural damage, and poor contact between active materials, thus affecting their rate performance and cycle life. Metal-organic frameworks (MOFs) are formed by the coordination of metal ions or metal clusters with organic ligands, and have the characteristics of tunable composition and relatively uniform distribution of metal elements. Thermal treatment using MOFs as precursors can yield metal compounds with more uniform composition and reduce particle size to some extent. Therefore, MOF derivatization provides a feasible route for preparing multi-component metal oxides. However, particle growth and agglomeration may still occur in MOF precursors during high-temperature conversion. For materials with low conductivity, such as ZnFe2O4 and Fe2O3, particle agglomeration increases the transport distance of electrons and ions, hindering electrochemical reactions. Carbon nanotubes possess excellent electronic conductivity, a large aspect ratio, and good flexibility. Adding carbon nanotubes to metal oxide materials can improve electron transport, and the one-dimensional structure of carbon nanotubes can also provide support and dispersion for active particles. However, the amount of carbon nanotubes added has a significant impact on the material structure. Insufficient addition makes it difficult to form a complete conductive network and fails to adequately improve particle agglomeration; excessive addition may lead to carbon nanotube entanglement and reduce the content of active components per unit mass of material.

[0004] Therefore, it is necessary to develop a ZnFe2O4 / Fe2O3-CNT composite anode material that has a simple preparation process, relatively uniform component distribution, and can improve the dispersion of active particles and electron transport by adjusting the carbon nanotube content. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries includes the following preparation steps: S1. By mass, add 1-2 parts of zinc nitrate hexahydrate, 0.5-1 parts of ferrous sulfate heptahydrate and 0.1-0.2 parts of modified cobalt source to 50-100 parts of methanol, stir thoroughly at room temperature for 8-10 minutes, and then sonicate for 8-10 minutes to obtain a metal mixture. S2. Add the metal mixture obtained in step S1 to 12-20 parts of structural modifier, stir and mix thoroughly at 300-500 r / min, transfer to a reaction vessel, and carry out a solvothermal reaction under heating conditions for 10-12 h to obtain the modified MOF / CNTs composite precursor. S3. Centrifuge the modified MOF / CNTs composite precursor and wash it with methanol 3-4 times. Then dry it in an oven at 78-80℃ for 10-12 hours to obtain the dried modified MOF / CNTs composite precursor. S4. The dried modified MOF / CNTs composite precursor was placed in a tube furnace and heat-treated under an argon protective atmosphere. The temperature was raised to 550-600℃ and held for 2-3 hours. After natural cooling, Co-ZnFe2O4 / Fe2O3-CNTs composite material was obtained. The preparation of the modified cobalt source includes the following steps: S11. By mass, add 0.1-0.2 parts of cobalt nitrate hexahydrate to 8-12 parts of deionized water, and stir magnetically at 400-600 r / min for 8-10 min at room temperature to obtain a mixture; S12. Add 0.05-0.10 parts of citric acid and 0.02-0.05 parts of ascorbic acid to the mixture obtained in step S11, and continue stirring at 400-600 r / min for 15-20 min to obtain the modified cobalt source.

[0007] Preferably, the preparation of the structure modifier includes the following steps: S21. By weight, add 1.8-3.6 parts of 2-methylimidazole and 10-20 parts of modified carbon nanotubes to 80-120 parts of methanol, and stir at 400-600 r / min for 10-15 min to obtain a mixture. S22. Add 0.2-0.5 parts of polyvinylpyrrolidone to the mixture obtained in step S21, continue stirring for 8-10 minutes, and then sonicate at a frequency of 40 kHz for 15-20 minutes to obtain the structure modifier.

[0008] Preferably, the preparation of modified carbon nanotubes includes the following steps: S211. By weight, add 10-20 parts of multi-walled carbon nanotubes to 50-80 parts of modified acid solution, stir magnetically at 300-500 r / min for 25-30 min at room temperature, then transfer to a water bath and reflux at 60-80℃ for 2-4 h. S212. The solution after reflux in step S211 is diluted with a large amount of deionized water, washed by centrifugation until the pH is 6-7, and then dried in an oven at 60-80℃ for 10-12 hours to finally obtain modified carbon nanotubes.

[0009] Preferably, the modified acid solution is composed of concentrated sulfuric acid, concentrated nitric acid, and hydrogen peroxide in a volume ratio of 3:1:0.5.

[0010] Preferably, the frequency of ultrasonic treatment in step S1 is 40 kHz.

[0011] Preferably, the stirring speed in step S1 is 400-600 r / min.

[0012] Preferably, the heating temperature in step S2 is 135-140℃.

[0013] Preferably, the heating rate in step S4 is 3-4℃ / min.

[0014] Preferably, the centrifugation speed in step S212 is 8000-10000 r / min.

[0015] A Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries is prepared by the above-described preparation method.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The modified carbon nanotubes of this invention are directly introduced during the precursor formation stage, enabling MOF-derived particles to form sufficient contact with CNTs, and forming a composite structure with particles loaded on the CNT framework after heat treatment. The modified carbon nanotubes improve the dispersion state of active particles and construct a continuous conductive network, thereby improving the electron transport capability and structural stability of the material.

[0017] 2. This invention achieves a dual-effect synergy of "ligand pre-anchoring - metal in-situ chelation" through the synergistic effect of modified cobalt source and structural modifier, forming high-density in-situ nucleation and uniform growth of MOF precursors on CNTs surface. The synergistic effect of the two constructs a three-dimensional high-efficiency electron transport system, significantly improving structural stability and capacity retention during cycling. Attached Figure Description

[0018] Figure 1 This is a process flow diagram for preparing the Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to the present invention; Figure 2 The images shown are SEM images of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention, where a is the SEM image at 10 μm; b is the SEM image at 1 μm; and c is the SEM image at 500 nm. Figure 3 The images shown are TEM images of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention, where a is a TEM image at 500 nm; b is a TEM image at 100 nm; and c is a TEM image at 50 nm. Figure 4 The XRD patterns are of the Co-ZnFe2O4 / Fe2O3-CNTs composite materials obtained in Examples 1-3 and Comparative Example 1 of this invention. Figure 5 The image shows the EDS diagram of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention. Detailed Implementation

[0019] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0020] Please see Figures 1-5 The present invention provides a technical solution: Example 1 A method for preparing Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries: Before preparing the Co-ZnFe2O4 / Fe2O3-CNTs composite material, the modified carbon nanotubes, modified cobalt source, and structural modifier were prepared: The preparation of modified carbon nanotubes includes the following steps: S211. Add 10g of multi-walled carbon nanotubes to 50g of modified acid solution (concentrated sulfuric acid, concentrated nitric acid, and hydrogen peroxide in a volume ratio of 3:1:0.5), stir magnetically at 300r / min for 25min at room temperature, and then transfer to a water bath and reflux at 60℃ for 2h. S212. The solution after reflux in step S211 is diluted with a large amount of deionized water, washed by centrifugation at 8000 r / min until the pH is 6, and then dried in an oven at 60℃ for 10 h to finally obtain modified carbon nanotubes.

[0021] The preparation of the modified cobalt source includes the following steps: S11. Add 0.1g of cobalt nitrate hexahydrate to 8g of deionized water and stir magnetically at 400r / min for 8min at room temperature to obtain a mixed solution; S12. Add 0.05g citric acid and 0.02g ascorbic acid to the mixture obtained in step S11, and continue stirring at 400r / min for 15min to obtain the modified cobalt source.

[0022] The preparation of the structural modifier includes the following steps: S21. Add 1.8g of 2-methylimidazole and 10g of modified carbon nanotubes to 80g of methanol, and stir at 400r / min for 10min to obtain a mixture; S22. Add 0.2g of polyvinylpyrrolidone to the mixture obtained in step S21, continue stirring for 8 minutes, and then sonicate at a frequency of 40kHz for 15 minutes to obtain the structure modifier.

[0023] The preparation of Co-ZnFe2O4 / Fe2O3-CNTs composite materials includes the following steps: S1. Add 1g of zinc nitrate hexahydrate, 0.5g of ferrous sulfate heptahydrate and 0.1g of modified cobalt source to 50g of methanol, stir thoroughly at 400r / min for 8min at room temperature, and then sonicate at 40kHz for 8min to obtain a metal mixture. S2. Add the metal mixture obtained in step S1 to 12g of structural modifier, stir and mix thoroughly at 300r / min, then transfer to a reaction vessel and carry out a solvothermal reaction at 135℃ for 10h to obtain the modified MOF / CNTs composite precursor. S3. The modified MOF / CNTs composite precursor was centrifuged and washed three times with methanol, and then dried in an oven at 78℃ for 10h to obtain the dried modified MOF / CNTs composite precursor. S4. The dried modified MOF / CNTs composite precursor was placed in a tube furnace and heat-treated under an argon protective atmosphere. The temperature was increased to 550℃ at 3℃ / min and held for 2h. After natural cooling, Co-ZnFe2O4 / Fe2O3-CNTs composite material was obtained.

[0024] Example 2 A method for preparing Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries: Before preparing the Co-ZnFe2O4 / Fe2O3-CNTs composite material, the modified carbon nanotubes, modified cobalt source, and structural modifier were prepared: The preparation of modified carbon nanotubes includes the following steps: S211. Add 20g of multi-walled carbon nanotubes to 80g of modified acid solution (concentrated sulfuric acid, concentrated nitric acid, and hydrogen peroxide in a volume ratio of 3:1:0.5), stir magnetically at 500r / min for 30min at room temperature, and then transfer to a water bath and reflux at 80℃ for 4h. S212. The solution after reflux in step S211 is diluted with a large amount of deionized water, washed by centrifugation at 10000 r / min until the pH is 7, and then dried in an oven at 80℃ for 12 h to finally obtain modified carbon nanotubes.

[0025] The preparation of the modified cobalt source includes the following steps: S11. Add 0.2g of cobalt nitrate hexahydrate to 12g of deionized water, and stir magnetically at 600r / min for 10min at room temperature to obtain a mixed solution; S12. Add 0.10g citric acid and 0.05g ascorbic acid to the mixture obtained in step S11, and continue stirring at 600r / min for 20min to obtain the modified cobalt source.

[0026] The preparation of the structural modifier includes the following steps: S21. Add 3.6g of 2-methylimidazole and 20g of modified carbon nanotubes to 120g of methanol, and stir at 600r / min for 15min to obtain a mixture; S22. Add 0.5g of polyvinylpyrrolidone to the mixture obtained in step S21, continue stirring for 10min, and then sonicate at 40kHz for 20min to obtain the structure modifier.

[0027] The preparation of Co-ZnFe2O4 / Fe2O3-CNTs composite materials includes the following steps: S1. Add 2g zinc nitrate hexahydrate, 1g ferrous sulfate heptahydrate and 0.2g modified cobalt source to 100g methanol, stir thoroughly at 600r / min for 10min at room temperature, and then sonicate at 40kHz for 10min to obtain a metal mixture. S2. Add the metal mixture obtained in step S1 to 20g of structural modifier, stir and mix thoroughly at 500r / min, then transfer to a reaction vessel and carry out a solvothermal reaction at 140℃ for 12h to obtain the modified MOF / CNTs composite precursor. S3. The modified MOF / CNTs composite precursor was centrifuged and washed four times with methanol, and then dried in an oven at 80℃ for 12h to obtain the dried modified MOF / CNTs composite precursor. S4. The dried modified MOF / CNTs composite precursor was placed in a tube furnace and heat-treated under an argon protective atmosphere. The temperature was increased to 600℃ at 4℃ / min and held for 3h. After natural cooling, Co-ZnFe2O4 / Fe2O3-CNTs composite material was obtained.

[0028] Example 3 A method for preparing Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries: Before preparing the Co-ZnFe2O4 / Fe2O3-CNTs composite material, the modified carbon nanotubes, modified cobalt source, and structural modifier were prepared: The preparation of modified carbon nanotubes includes the following steps: S211. Add 15g of multi-walled carbon nanotubes to 60g of modified acid solution (concentrated sulfuric acid, concentrated nitric acid, and hydrogen peroxide in a volume ratio of 3:1:0.5), stir magnetically at 400r / min for 27min at room temperature, and then transfer to a water bath and reflux at 70℃ for 3h. S212. The solution after reflux in step S211 is diluted with a large amount of deionized water, washed by centrifugation at 9000 r / min until the pH is 6.5, and then dried in an oven at 70℃ for 11 h to finally obtain modified carbon nanotubes.

[0029] The preparation of modified cobalt sources includes the following steps: S11. Add 0.15g of cobalt nitrate hexahydrate to 10g of deionized water, and stir magnetically at 200r / min for 9min at room temperature to obtain a mixed solution; S12. Add 0.07g citric acid and 0.03g ascorbic acid to the mixture obtained in step S11, and continue stirring at 500r / min for 18min to obtain the modified cobalt source.

[0030] The preparation of the structural modifier includes the following steps: S21. Add 2.2g of 2-methylimidazole and 15g of modified carbon nanotubes to 100g of methanol, and stir at 500r / min for 13min to obtain a mixture; S22. Add 0.3g of polyvinylpyrrolidone to the mixture obtained in step S21, continue stirring for 9 minutes, and then sonicate at a frequency of 40kHz for 18 minutes to obtain the structure modifier.

[0031] The preparation of Co-ZnFe2O4 / Fe2O3-CNTs composite materials includes the following steps: S1. Add 1.5g zinc nitrate hexahydrate, 0.8g ferrous sulfate heptahydrate and 0.15g modified cobalt source to 80g methanol, stir thoroughly at 500r / min for 9min at room temperature, and then sonicate at 40kHz for 9min to obtain a metal mixture. S2. Add the metal mixture obtained in step S1 to 16g of structural modifier, stir and mix thoroughly at 400r / min, then transfer to a reaction vessel and carry out a solvothermal reaction at 138℃ for 11h to obtain the modified MOF / CNTs composite precursor. S3. The modified MOF / CNTs composite precursor was centrifuged and washed four times with methanol, and then dried in an oven at 79℃ for 11h to obtain the dried modified MOF / CNTs composite precursor. S4. The dried modified MOF / CNTs composite precursor was placed in a tube furnace and heat-treated under an argon protective atmosphere. The temperature was increased to 580℃ at 3.5℃ / min and held for 2.5h. After natural cooling, Co-ZnFe2O4 / Fe2O3-CNTs composite material was obtained.

[0032] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that no modified carbon nanotubes were added in this comparative example; the other steps are exactly the same in Comparative Example 1 and Example 1.

[0033] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the modified cobalt source is replaced with cobalt nitrate hexahydrate in this comparative example. The remaining steps are exactly the same in Comparative Example 2 and Example 1.

[0034] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that no structural modifier was added in this comparative example; the other steps are exactly the same in Comparative Example 3 and Example 1.

[0035] Performance testing: The Co-ZnFe2O4 / Fe2O3-CNTs composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were used as the active materials for the negative electrode. The negative electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) binder were mixed in a mass ratio of 7:2:1 and thoroughly ground in N-methylpyrrolidone (NMP) solvent to form a uniform slurry. The resulting slurry was then coated onto an area of ​​1.539 cm². 2 The negative electrode is a copper foil coated with carbon. The positive electrode is a lithium metal sheet. The electrolyte is a 1.0 M LiPF6 solution dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The separator is a Whatman GF / F glass fiber membrane. The lithium-ion battery was assembled in a glove box under high-purity argon protection, where the oxygen and moisture content were both no higher than 0.1 ppm. Performance testing was performed after assembly. The final test results are shown in Table 1 below. Table 1. Performance Test Results As shown in Table 1, the lithium-ion batteries assembled using the Co-ZnFe2O4 / Fe2O3-CNTs composite materials obtained in Examples 1-3 as the negative electrode active material exhibit significantly improved cycle stability compared to the comparative examples. This indicates that the present invention constructs a three-dimensional high-efficiency electron transport system through the synergistic effect of modified carbon nanotubes, a modified cobalt source, and a structural modifier, significantly improving structural stability and capacity retention during cycling.

[0036] Appendix Figure 2 This is a SEM image of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention. As shown in the image, the composite material exhibits a distinct particle / CNTs composite structure, with oxide particles uniformly distributed within the network structure formed by modified carbon nanotubes, and no obvious large-size particle agglomeration is observed. With the introduction of modified carbon nanotubes, they can serve as a structural support framework, effectively dispersing MOF-derived oxide particles, thereby improving the structural stability of the active material.

[0037] Appendix Figure 3 This is a TEM image of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention. The image shows a large number of nanoparticles uniformly loaded on the surface of the modified carbon nanotubes, forming a tightly contacted particle / CNTs composite structure. The modified carbon nanotubes act as continuous conductive channels connecting the dispersed oxide nanoparticles, facilitating rapid electron transport within the electrode. Simultaneously, the nano-sized oxide particles can shorten the Li... + Diffusion pathways improve electrode reaction kinetics.

[0038] Appendix Figure 4 The figures show the XRD patterns of the Co-ZnFe2O4 / Fe2O3-CNTs composite materials obtained in Examples 1-3 and Comparative Example 1 of this invention. As can be seen from the figures, the samples from each example exhibit characteristic diffraction peaks of ZnFe2O4 and Fe2O3, indicating that the MOF precursor successfully formed a composite oxide structure after thermal conversion. Even after introducing modified carbon nanotubes, the material still maintains a good crystal structure, indicating that the addition of CNTs does not destroy the oxide crystal structure and can help stabilize the MOF-derived oxide particles.

[0039] Appendix Figure 5 This is the EDS diagram of the Co-ZnFe2O4 / Fe2O3-CNTs composite material obtained in Example 2 of this invention. The results of the elemental analysis in the diagram are consistent with those of the XRD phase analysis, proving that Co has been successfully doped into the composite oxide system, inducing lattice distortion and oxygen vacancies, which helps to improve the intrinsic electronic conductivity and electrochemical reactivity of the material.

[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries, characterized in that, The preparation steps include the following: S1. By mass, add 1-2 parts of zinc nitrate hexahydrate, 0.5-1 parts of ferrous sulfate heptahydrate and 0.1-0.2 parts of modified cobalt source to 50-100 parts of methanol, stir thoroughly at room temperature for 8-10 minutes, and then sonicate for 8-10 minutes to obtain a metal mixture. S2. Add the metal mixture obtained in step S1 to 12-20 parts of structural modifier, stir and mix thoroughly at 300-500 r / min, then transfer to a reaction vessel and carry out a solvothermal reaction under heating conditions for 10-12 h to obtain the modified MOF / CNTs composite precursor. S3. Centrifuge the modified MOF / CNTs composite precursor and wash it with methanol 3-4 times. Then dry it in an oven at 78-80℃ for 10-12 hours to obtain the dried modified MOF / CNTs composite precursor. S4. The dried modified MOF / CNTs composite precursor was placed in a tube furnace and heat-treated under an argon protective atmosphere. The temperature was raised to 550-600℃ and held for 2-3 hours. After natural cooling, Co-ZnFe2O4 / Fe2O3-CNTs composite material was obtained. The preparation of the modified cobalt source includes the following steps: S11. By mass, add 0.1-0.2 parts of cobalt nitrate hexahydrate to 8-12 parts of deionized water, and stir magnetically at 400-600 r / min for 8-10 min at room temperature to obtain a mixture; S12. Add 0.05-0.10 parts of citric acid and 0.02-0.05 parts of ascorbic acid to the mixture obtained in step S11, and continue stirring at 400-600 r / min for 15-20 min to obtain the modified cobalt source; The structural modifier was prepared by 2-methylimidazole, modified carbon nanotubes, methanol, and polyvinylpyrrolidone. The modified carbon nanotubes were prepared by using multi-walled carbon nanotubes, modified acid solution, and deionized water.

2. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The preparation of the structural modifier includes the following steps: S21. By weight, add 1.8-3.6 parts of 2-methylimidazole and 10-20 parts of modified carbon nanotubes to 80-120 parts of methanol, and stir at 400-600 r / min for 10-15 min to obtain a mixture. S22. Add 0.2-0.5 parts of polyvinylpyrrolidone to the mixture obtained in step S21, continue stirring for 8-10 minutes, and then sonicate at a frequency of 40 kHz for 15-20 minutes to obtain the structure modifier.

3. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The preparation of the modified carbon nanotubes includes the following steps: S211. By weight, add 10-20 parts of multi-walled carbon nanotubes to 50-80 parts of modified acid solution, stir magnetically at 300-500 r / min for 25-30 min at room temperature, then transfer to a water bath and reflux at 60-80℃ for 2-4 h. S212. The solution after reflux in step S211 is diluted with a large amount of deionized water, washed by centrifugation until the pH is 6-7, and then dried in an oven at 60-80℃ for 10-12 hours to finally obtain modified carbon nanotubes.

4. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The modified acid solution is composed of concentrated sulfuric acid, concentrated nitric acid, and hydrogen peroxide in a volume ratio of 3:1:0.

5.

5. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The frequency of the ultrasonic treatment in step S1 is 40 kHz.

6. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The stirring speed in step S1 is 400-600 r / min.

7. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The heating temperature in step S2 is 135-140℃.

8. The method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 1, characterized in that, The heating rate in step S4 is 3-4℃ / min.

9. A method for preparing a Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries according to claim 3, characterized in that, The centrifugation speed in step S212 is 8000-10000 r / min.

10. A Co-ZnFe2O4 / Fe2O3-CNTs composite material for lithium-ion batteries, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.